Analysis Of Latest And Contextual Aspects Of Physics E-Module Based On T-Pack Momentum Impulse Materials For Class X Students - Simatun Ni'mah; Umi Uswatun; Silvia Yusiana Andarini; Tsamaratul Fuadiyah; Akhmad Khanafi; Netty Berliana Herman; I Ketut Mahardika; Subiki Subiki (FKIP, Universitas Palangka Raya, 2023)
Learning media can be defined as an important element in a learning process. One example of learning media is teaching materials in the form of Emodules which in Emodules in this study use momentum and impulse material. One of the materials studied in physics is momentum and impulse. Momentum is a vector quantity so it has both magnitude and direction. Impulse itself is a force event that acts on an object in a short period. This type of research uses Research and Development (R&D) in the Tessmer development model which is also contained in the appendix. The stages are divided into two, including self-evaluation which is a determinant of the design features or specifications of the module. Prototyping where there are teaching modules will later be validated, evaluated, and revised. From the results of the module validation carried out by the examiners as experts, a review was carried out and a score was given to the module, namely, 91.2% consisting of image actualization of 75 points, in the aspect of modernity of the library, a score of 100 was obtained.